2017
DOI: 10.1111/1365-2664.12870
|View full text |Cite
|
Sign up to set email alerts
|

When road‐kill hotspots do not indicate the best sites for road‐kill mitigation

Abstract: Summary The effectiveness of measures installed to mitigate wildlife road‐kill depends on their placement along the road. Road‐kill hotspots are frequently used to identify priority locations for mitigation measures. However, in situations where previous road mortality has reduced population size, road‐kill hotspots may not indicate the best sites for mitigation. The purpose of this study was to identify circumstances in which road‐kill hotspots are not appropriate indicators for the selection of the best ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 29 publications
3
43
1
1
Order By: Relevance
“…They include, but are not limited to, understanding of wildlife movements and behaviours, localisation of wildlife corridors [38,[47][48][49], knowledge of population density [50], population dynamics and habitat properties. In line with other authors [15,51,52] we also con rm that placing of mitigation measures is challenging, due to the lack of knowledge on the local spatial-temporal patterns of wildlife dynamics, including population, behaviour, pathways and habitat suitability [13].…”
Section: Evaluation Of Wildlife Fencessupporting
confidence: 90%
“…They include, but are not limited to, understanding of wildlife movements and behaviours, localisation of wildlife corridors [38,[47][48][49], knowledge of population density [50], population dynamics and habitat properties. In line with other authors [15,51,52] we also con rm that placing of mitigation measures is challenging, due to the lack of knowledge on the local spatial-temporal patterns of wildlife dynamics, including population, behaviour, pathways and habitat suitability [13].…”
Section: Evaluation Of Wildlife Fencessupporting
confidence: 90%
“…However, we stress that results concerning roadkill hotspots have to be carefully interpreted. Teixeira et al (2017) showed that hotspot locations may shift in place with time. Therefore, continued monitoring may be required, even if road sections with a hotspot in road mortality have been mitigated.…”
Section: Roadkill Hotspotsmentioning
confidence: 99%
“…Because it is currently unrealistic and cost prohibitive to mitigate all roadways for all species, it is vital to identify species most susceptible to road-related impacts. Within species ranges, risks to populations and need for mitigation can then be evaluated based upon local road densities and matrix, road-types, traffic, and road locations in relation to species habitat and movement corridors (e.g., Jaeger 2000; Litvaitis and Tash 2008;Langen et al 2015b;Zimmermann Teixeira et al 2017).…”
Section: Introductionmentioning
confidence: 99%